1993
DOI: 10.1080/10587259308036231
|View full text |Cite
|
Sign up to set email alerts
|

Alkylene Polyimides for Aligning Nematic Liquid Crystals: Anomalous Odd-Even Effect in Tilt Bias Angles as a Function of Chain Length of Alkylenes

Abstract: Measurements of tilt bias angles of a nematic liquid crystal were carried out, by using several alkylene polyimides synthesized from 3,3',4,4'-biphenyltetracarboxylic dianhydrides and diamines with different chain lengths as alignment layers. The tilt bias angle dependence on the alkylene chain length of polyimides shows an anomalous odd-even effect. Small tilt bias angles, less than one degree, were observed with odd-number alkylene chain lengths. Relatively high tilt bias angles, however, were observed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…1,2 Rubbed polyimide ͑PI͒ films have been widely used to align LC molecules, but the detailed mechanism of LC alignment is not yet fully understood. Most recently, oddeven effects of the alkyl chain length on pretilt angles of LC on rubbed PI films has been reported by Yokokura et al 3 High pretilt angles were observed on rubbed PI films with an even number of carbons in the alkyl chain. 3 The odd-even effect in pretilt angles and orientational order of LCs on rubbed PI surfaces was measured by Johannsmann et al using surface optical second harmonic generation ͑SHG͒ and birefringence measurements.…”
Section: Division Of Electronic and Information Engineering Faculty mentioning
confidence: 90%
See 1 more Smart Citation
“…1,2 Rubbed polyimide ͑PI͒ films have been widely used to align LC molecules, but the detailed mechanism of LC alignment is not yet fully understood. Most recently, oddeven effects of the alkyl chain length on pretilt angles of LC on rubbed PI films has been reported by Yokokura et al 3 High pretilt angles were observed on rubbed PI films with an even number of carbons in the alkyl chain. 3 The odd-even effect in pretilt angles and orientational order of LCs on rubbed PI surfaces was measured by Johannsmann et al using surface optical second harmonic generation ͑SHG͒ and birefringence measurements.…”
Section: Division Of Electronic and Information Engineering Faculty mentioning
confidence: 90%
“…Most recently, oddeven effects of the alkyl chain length on pretilt angles of LC on rubbed PI films has been reported by Yokokura et al 3 High pretilt angles were observed on rubbed PI films with an even number of carbons in the alkyl chain. 3 The odd-even effect in pretilt angles and orientational order of LCs on rubbed PI surfaces was measured by Johannsmann et al using surface optical second harmonic generation ͑SHG͒ and birefringence measurements. 4 They demonstrated that PI surfaces with even numbers of carbon in the alkyl side chain are smoother and capable of inducing higher surface order in an 8CB surface layer.…”
Section: Division Of Electronic and Information Engineering Faculty mentioning
confidence: 90%
“…It is interesting to note the "odd-even" behavior of the tensile properties of polymer VIII films similar to the reported behavior of the melting temperatures for these polymers 18 and for analogous aliphatic PIs 26,27 and as reported in the behavior of the tilt bias angle for aliphatic PIs. 28 Thus, tensile strengths at break and initial moduli of polymers with an even number of methylene spacers have larger values than those of polymers with an odd number of methylene spacers.…”
Section: Properties Of Polymersmentioning
confidence: 98%
“…The system chosen was a surface monolayer of 8CB on a surface of poly-m-alkanpyromellitimide ͑poly-m-APM͒, where m is the number of CH 2 units between the imide moieties. 45 The chemical structures are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%